Decreasing ADHD phenotypic heterogeneity: searching for neurobiological underpinnings of the restrictive inattentive phenotype - Ercan, Eyup Sabri; Suren, Serkan; Bacanli, Ali; Yazici, Kemal Utku; Calli, Cem; Ozyurt, Onur; Rohde, Luis Augusto (Springer, 2016)
During the process of developing the DSM-5, a new phenotype of ADHD was proposed-the ADHD restrictive inattentive presentation (ADHD-RI), describing subjects with high endorsement of inattentive symptoms and a low level of hyperactivity. However, this phenotype was not included in the DSM-5 because of the lack of robust neurobiological data. We aimed to assess the specific neurobiological underpinnings of individuals presenting ADHD-RI. We compared a sample of 301 subjects (101 ADHD-Combined; 50 ADHD-RI; 50 ADHD predominantly inattentive type and 100 typically developing subjects) aged 8-15 years, using a complete neuropsychological battery, molecular genetic data (DRD4 and DAT1 most studied polymorphisms) and functional MRI during a Go-No/Go task. Subjects with ADHD-RI had a significantly different neuropsychological profile compared with the other groups, including lower psychomotor speeds, longer reaction times and the worst overall performance in the global neurocognitive index. The proportion of subjects with the presence of DRD4-7 repeat allele was significantly higher in ADHD-RI. The fMRI data suggested that more attention-related posterior brain regions (especially temporo-occipital areas) are activated in ADHD-RI during both Go and No-Go cues compared to TD controls and ADHD predominantly inattentive type. ADHD-RI may represent a different phenotype than other types of ADHD. In addition, our results suggest that reducing the phenotypic heterogeneity may aid in the search for the neurobiological underpinnings of ADHD.
Keywords: ADHD; Phenotype; Neuropsychology; Neuroimaging; Molecular genetics; Hyperactivity